Differenciated Approach as the Means of Developing Cognitive Skills at a Music’s Lesson - Dolidze, Dali (International Scientific Conference “EDUCATION, RESEARCH, PRACTICE” Proceedings, 2024)
Modern standards are widely aimed at the humanization of education and the individualization of teaching, which contributes to the development of a student. Differentiated teaching approaches are an effective way to fulfill this requirement. We often use similar approaches in practice. For example, when we plan a lesson, we try to answer the question: how to achieve that a student does not just memorize a certain amount of information, but learns regardless of what means and what potential he has. Individualization and differentiation of teaching in music lessons enable each student to understand themselves and the teacher to find ways of transferring the teaching material to the majority and to encourage students. Advantages of differentiated teaching: difficulties are easily overcome; no students are falling behind in the class; All students are involved in the learning process; Personal qualities are actively formed; independence, diligence, self-confidence, creativity, motivation, and curiosity increase; the content is actively being processed; students prepare in advance for such work; the process is easy to monitor. A differentiated approach encourages low-achieving students by helping them see their knowledge gaps and learning abilities more broadly. As a result, they constantly maintain an interest in the subject.